2017
DOI: 10.1021/acs.nanolett.6b04698
|View full text |Cite
|
Sign up to set email alerts
|

Stacking-Dependent Electronic Structure of Trilayer Graphene Resolved by Nanospot Angle-Resolved Photoemission Spectroscopy

Abstract: The crystallographic stacking order in multilayer graphene plays an important role in determining its electronic structure. In trilayer graphene, rhombohedral stacking (ABC) is particularly intriguing, exhibiting a flat band with an electric-field tunable band gap. Such electronic structure is distinct from simple hexagonal stacking (AAA) or typical Bernal stacking (ABA), and is promising for nanoscale electronics, optoelectronics applications. So far clean experimental electronic spectra on the first two stac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 43 publications
(130 reference statements)
5
65
1
1
Order By: Relevance
“…On the other hand, monolayer tine exhibit the very strong multi-orbital hybridizations and SOCs, [135] so that the outside four orbitals (5s, 5p x , 5p y , 5p z ) need to be considered in the low-energy band structures. The calculated electronic energy spectra could be verified from the ARPES measurements, [56,57,[65][66][67][68][111][112][113][114] as done for few-layer graphenes and graphites.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…On the other hand, monolayer tine exhibit the very strong multi-orbital hybridizations and SOCs, [135] so that the outside four orbitals (5s, 5p x , 5p y , 5p z ) need to be considered in the low-energy band structures. The calculated electronic energy spectra could be verified from the ARPES measurements, [56,57,[65][66][67][68][111][112][113][114] as done for few-layer graphenes and graphites.…”
Section: Introductionmentioning
confidence: 62%
“…The experimental measurements have confirmed the geometry-enriched band structures in the graphene-related condensed-matter systems, as verified for various dimensions, layer numbers, stacking symmetries, and adatom/molecule chemisorptions. There exist (k x , k y , k z )-dependent 3D band structures of Bernal graphite, [111][112][113][114] 1D parabolic energy subbands in graphene nanoribbons, [157,158] the linearly isotropic Dirac-cone structure in monolayer graphene, [45,159] and few-layer AA-stacked graphene, [56,57] two pairs of parabolic dispersions in AB-stacked bilayer graphene, [65][66][67][68] the coexistent linear and parabolic bands in symmetry-broken bilayer graphene, [160] the linear and parabolic bands in trilayer graphene with ABA stacking, [66][67][68] the linear, partially flat and sombrero-shaped bands in ABC-stacked trilayer graphene, [66][67][68] the metal-semiconductor transitions and the tunable low-lying energy bands after the molecule/adatom absorptions on graphene surface. [161] On the other side, the predicted Coulomb decay rates could be examined from the high-resolution ARPES measurements on the energy widths, as clearly revealed in potassium chemiadsorption on monolayer graphene.…”
Section: Arpes Measurements On Occupied Quasi-particle Energy Widthsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) The Dirac cone structure of trilayer graphene displays qualitatively different behavior in each of its three different stacking configurations, adapted with permission from Ref. [30]. Copyright 2017, American Chemical Society.…”
Section: Phononic Bilayer Graphenementioning
confidence: 99%
“…In fact, previous angle-resolved photoemission spectroscopy (ARPES) studies on epitaxially grown TL graphene have suggested the mixture of ABA and ABC domains in a film. [18][19][20] In addition, TL graphene grown on an SiC substrate exhibits a metallic character because of charge transfer from the substrate through a buffer layer with a graphene-like structure. 15 Therefore, graphitization of the buffer layer and the reduction of interference from the substrate are essential to revealing the intrinsic electronic properties of genuine TL graphene.…”
Section: Introductionmentioning
confidence: 99%